Melatonin reduces angiogenesis in serous papillary ovarian carcinoma of ethanol-preferring rats - Zonta, Yohan Ricci [UNESP]; Martinez, Marcelo; Camargo, Isabel Cristina C. [UNESP]; Domeniconi, Raquel F. [UNESP]; Lupi Júnior, Luiz Antonio [UNESP]; Pinheiro, Patricia Fernanda F. [UNESP]; Reiter, Russel J.; Martinez, Francisco Eduardo [UNESP]; Chuffa, Luiz Gustavo A. [UNESP] (MDPI, 2017)
Angiogenesis is a hallmark of ovarian cancer (OC); the ingrowth of blood vessels promotes rapid cell growth and the associated metastasis. Melatonin is a well-characterized indoleamine that possesses important anti-angiogenic properties in a set of aggressive solid tumors. Herein, we evaluated the role of melatonin therapy on the angiogenic signaling pathway in OC of an ethanol-preferring rat model that mimics the same pathophysiological conditions occurring in women. OC was chemically induced with a single injection of 7,12-dimethylbenz(a)anthracene (DMBA) under the ovarian bursa. After the rats developed serous papillary OC, half of the animals received intraperitoneal injections of melatonin (200 µg/100 g body weight/day) for 60 days. Melatonin-treated animals showed a significant reduction in OC size and microvessel density. Serum levels of melatonin were higher following therapy, and the expression of its receptor MT1 was significantly increased in OC-bearing rats, regardless of ethanol intake. TGFβ1, a transforming growth factor-beta1, was reduced only after melatonin treatment. Importantly, vascular endothelial growth factor (VEGF) was severely reduced after melatonin therapy in animals given or not given ethanol. Conversely, the levels of VEGF receptor 1 (VEGFR1) was diminished after ethanol consumption, regardless of melatonin therapy, and VEGFR2 was only reduced following melatonin. Hypoxia-inducible factor (HIF)-1α was augmented with ethanol consumption, and, notably, melatonin significantly reduced their levels. Collectively, our results suggest that melatonin attenuates angiogenesis in OC in an animal model of ethanol consumption; this provides a possible complementary therapeutic opportunity for concurrent OC chemotherapy.
Keywords: Angiogenesis; Hypoxia-inducible factor (HIF)-1α; Melatonin; Ovarian cancer; VEGF (vascular endothelial growth factor); VEGFR (VEGF receptor)